ROLE OF MICROWAVE ENERGY TO CONTROL THREE SPECIES OF STORE PRODUCTS INSECTS - Aead Y. Ismail (Mesopotamia Journal of Agriculture)
Three levels of microwave energy low ,medium& ,high. 260,520 and 780 w, respectively were used to control three species of the saw-toothed grain beetle Oryzaephilus surinamensis L.,Red flour beetle Tribolium castaneum Herbst,the Khapra beetle Trogoderma granarium Evert in Store Products ,viz. Jrush ,Burglar and Habia at three exposure periods 1,1.5 and 2 minutes. The results showed that the highest mortality percentage occupied in Oryzaephilus surinamensis 75.67%,followed by Tribolium castaneum which was 68.64% while the lower was 66.29% in case of Trogoderma granarium. Highest energy level gave 100% mortality percentage ,while the medium level gave 99.63% percentage whereas only 10.98% percentage was recorded with low level.The highest percent mortality in Burglar 71.48% while the lower was in Habia 67.9%. Exposure periods of 1.0,1.5 and 2 minutes gave 75.18 , 68.64 and 66.79% mortality percentage, respectively . The temperature produced was almost similar in three products ; 69.77 ,73.88 and 72.77 °C while that of control treatment was 25.33°C.The temperature of microwave energy level were 87.08, 62.41 and 31.83°C for high ,medium and low, respectively .